2018
DOI: 10.1111/hiv.12668
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for loss to follow‐up, transfer or death among people living with HIV on their first antiretroviral therapy regimen in Mali

Abstract: Objectives Risk factors for loss to follow‐up (LTFU) were assessed for people living with HIV (PLHIV) at various reference out‐patient clinics (expertise level II) and hospitals (expertise level III) in Mali. Methods HIV‐1‐positive adults starting antiretroviral therapy (ART) in 2006–2013 were eligible for inclusion. Risk factors for LTFU, defined as no visit in the 6 months preceding the last database update, were assessed with the Cox model, taking into account the competing risks of transfer and death. Pote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
9
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 19 publications
4
9
1
Order By: Relevance
“…We did not have the possibility to assess those data, or to assess social support from the family and the community, and HIV status disclosure. We also did not show differences according to social data such as educational level contrary to what has been shown in studies of LTFU risk factors [8,41]. However, difficulties to return to care when living more than 5 km to the care centre in the regions could be due to financial or transportation issues.…”
Section: Discussioncontrasting
confidence: 89%
See 3 more Smart Citations
“…We did not have the possibility to assess those data, or to assess social support from the family and the community, and HIV status disclosure. We also did not show differences according to social data such as educational level contrary to what has been shown in studies of LTFU risk factors [8,41]. However, difficulties to return to care when living more than 5 km to the care centre in the regions could be due to financial or transportation issues.…”
Section: Discussioncontrasting
confidence: 89%
“…ART programme is often faced with issues of reagents out of stock and VL device maintenance. The ESTHER initiative [10] focused on reinforcing the clinical skills and capacity of health professionals through peer-to-peer partnerships between French hospitals and their African counterparts and provided an electronic medical records system "Evaluation et Suivi Opérationnel des Programmes d'ESTHER" (ESOPE, Epiconcept, France) for monitoring PLHIV care and the effectiveness of ART, which was progressively implemented at five reference outpatient clinics and two hospitals in Bamako, and at four reference outpatient clinics and five hospitals in five regions (Fig 1), as previously described [8]. The PLHIV included in the ESOPE database accounted for 64% of the 51,000 PLHIV in healthcare for HIV in Mali at the last database update on March 31, 2015 [11].…”
Section: Study Settingmentioning
confidence: 99%
See 2 more Smart Citations
“…The possible justification could be due to the fact that children living in rural areas travel long distances to get access to ART. Studies suggested that patients living far from a health facility had a greater risk of LTFU [34,35]. Moreover, children living in rural areas could have difficulties to access favorable transportation; as a result, they could miss their appointments.…”
Section: Plos Onementioning
confidence: 99%